2020
DOI: 10.1590/1980-0037.2020v22e75400
|View full text |Cite
|
Sign up to set email alerts
|

“Cross” modalities: are the AMRAP, RFT and EMOM models applicable to health?

Abstract: Currently, training models based on the maximum number of repetitions/rounds or on the execution of a proposed task in the shortest possible time have been gaining ground among Physical Education professionals. However, in our opinion, these models have significant drawbacks that oppose their use in the health context. Thus, we provide an analysis of the problems related to the control and magnitude of the training load (volume and intensity), distribution, duration, and characteristics of the recovery interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Besides, depending on the velocity loss they reach over the set time, they will perform a higher number of repetitions/rounds in the pre-defined total time. In this way, the subject who could initially perform better would be the one who trains with less relative intensity, being able to perform the exercises at a higher velocity and possibly with a lesser velocity loss in the set, compared to those who perform the same number of repetitions with the same absolute load, which represents a higher relative intensity (Silva-Grigoletto et al, 2020). The AMRAP method could produce a significant increased in maximal aerobic capacity, an increased in maximal oxygen consumption expressed as a function of body mass was significantly correlated with an increased in absolute oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, depending on the velocity loss they reach over the set time, they will perform a higher number of repetitions/rounds in the pre-defined total time. In this way, the subject who could initially perform better would be the one who trains with less relative intensity, being able to perform the exercises at a higher velocity and possibly with a lesser velocity loss in the set, compared to those who perform the same number of repetitions with the same absolute load, which represents a higher relative intensity (Silva-Grigoletto et al, 2020). The AMRAP method could produce a significant increased in maximal aerobic capacity, an increased in maximal oxygen consumption expressed as a function of body mass was significantly correlated with an increased in absolute oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified situations of rhabdomyolysis related to this type of high-intensity effort [47][48][49]. Hence, it is likely that all-out training through FFT tactics such as AMRAP, RFT, or EMON (every minute on the minute) could have adverse health impacts [11]. In a recent study, Alsamir Tibana et al (2019) [46] tried to determine whether self-regulation of training intensity based on RPE is a reliable method to control work intensity during metabolic conditioning sessions of FFT.…”
Section: Discussionmentioning
confidence: 99%
“…Another difference between HIIT and FFT is that the latter lacks prescribed rest intervals [1]. Many FFT workouts consist of completing a set number of repetitions in the shortest time possible ("rounds for time") or completing within a set time frame as many repetitions as possible ("AMRAP") of a set of exercises [1,11]. Hence, rest or recovery intervals are introduced by athletes "as needed" depending on their physical fitness level or the nature of the FFT workout.…”
Section: Introductionmentioning
confidence: 99%
“…In the AMRAP model, the largest possible task volume (number of repetitions or rounds) is performed in a fixed time interval. In the EMOM model, the exercise must be performed within one minute, while in the FT model, the proposed task must be completed in the shortest time possible [9,11]. In addition to the AMRAP, the EMOM and FT models can also have a fixed total time interval or a time cap for task conclusion.…”
Section: "Cross" Modalitiesmentioning
confidence: 99%